Autismo e surdez: uma análise das estratégias de comunicação e autoeficácia docente em escolas bilíngues para surdos - Lopes, Raquel Aparecida (2019)
The presence of students with ASD (Autism Spectrum Disorder) has become commonplace in Municipal Bilingual Education Schools for the Deaf and in the bilingual center for deaf children in the regular schools. This condition is characterized by deficits related to the disorder and the absence of hearing and often causes inability to develop communication. Although this situation may lead to impairment, these students may benefit from some strategies in the school environment, when they are adjusted to their communicative needs. This encourages discussion about the difficulties faced by teachers and corroborates the questions about the communication tools used in the classroom. In view of the circumstances, in the teacher´s opinion, is it possible to propose the Brazilian Sign Language , as a communication tool for these students? Is the current classroom model in which they are inserted best suited to develop their skills? Do these teachers feel able to develop pedagogical actions effectively? Based on these questions, this study aims to verify, in a group of teachers, the possibility of using the Brazilian Sign Language as a communication tool for students with ASD deaf. In addition to this aim, the following specific objectives were also considered: identify the profile of these professionals; analyze their conceptions and opinions about which school is best suited for the student’s skills development; analyze the communicative strategies used in the classroom; identify teacher´s perceptions of self-efficacy, regarding working with students with ASD. The research design consisted in an exploratory survey study of quantitative and qualitative approach, two instruments were used:the first was a 12-question questionnaire and the second was the ASSET - Autism Self-Efficacy Scale for Teachers, validated and published in Portuguese. Both were applied to 38 teachers through an online platform, accessed at https://docs.google.com. The results were reported in four studies: (Study I): indicates that most teachers are female (89.5%), resident of the Southeast region of Brazil, most with Lato Sensu Postgraduate level (78.7%).(Study II) points out that these professionals correctly recognize the presence of factors associated with deficits in student´s socio-communicative and behavioral dimensions, however, almost half consider that training in this area is offered superficially. (Study III): points out that Brazilian Sign Language is the most used communication strategy in the classroom (86.8%), but approximately half of the teachers agree that these students would develop better if they were not inserted in joint classrooms in bilingual schools (47.4%), in the opinion of (28.9%) these students should study in joint classrooms with the deaf, however, for (23.7%) they should be included in regular schools. (Study IV): The ASSET results show that most participants are confident with the items evaluated, which may be a potential predictor of teaching attitudes in bilingual educational contexts. These results highlight the importance of self-assessment instruments for professionals working in the education of deaf ASD people in Brazil.